А Вісла дале плыне Петра Мурянкы – автобіоґрафія як реінвенцийний міф - Olena Duć-Fajfer (Ksiegarnia Akademicka Publishing, 2018)
And the Vistula Flows On by Petr Murianka – Autobiography as Reinvention Myth The article attempts to symptomatically read one of the most important texts in Lemko literature of the last decades – the literary autobiography of Petr Murianka entitled And the Vistula Flows On. A large textual machine working for a reinvented myth has been presented, which after the resettlement is to create a new narrative of the community. The Lemko myth works in defiance of the flowing Vistula River, that is, symbolically saving the order of the world with the homeland still remaining in the mountains and foreign lands where Lemkos were resettled. The autobiography was created 60 years after the destructive dislocation of Lemko population and is a testimony of persistent opposition to Polonisation highly determined by displacement. Dedicated to Polish neighbours and written in Lemko Polish, it contains a number of strategic elements acting in a myth-making way and at the same time performatively. What is characteristic for the autobiography - when establishing a pact with the reader it refers to his own people (the myth making pact) and to the neighbours (the pact of understanding). What was published with the aim of ‘describing life’ as an autobiography of a sixty-year-old is, first and foremost, an (auto)biography of a community which for sixty years has been drowning in the dominant trend of disenchanted history.